Update on Collagens: What You Need to Know and Consider. Issue 4 (October 2019) - Barnes, Marcia
Abstract : The prevalence of chronic wounds remains a concern for wound care providers. Additional therapies that promote wound healing continue to be on the forefront of wound care. Selecting treatment modalities should be based on current evidence and a critical analysis of that evidence. However, evidence in wound care in the form of randomized controlled trials is lacking. This article describes collagen, its use in wound care, and current evidence for review.